Pandangan Islam dalam Pengembangan Ekonomi di Era Digital - Daim, Daim (Lembaga Kajian dan Penerapan Nilai - Nilai Islam Unissula, 2023)
Globalization has brought major changes to the world economic system, creating challenges as well as opportunities for Muslim countries to integrate Islamic economic principles in facing global market dynamics. This article discusses the Islamic worldview in the context of economic development in the era of globalization, by highlighting the main concepts of Islamic economics, such as monotheism, justice, balance and social responsibility. Although capitalist economic systems and socialism dominate in many parts of the world, Islam offers an alternative that emphasizes shared prosperity, sustainable resource management, and fair distribution of wealth through sharia-based mechanisms of zakat, alms, and investment. This article also identifies the challenges faced by Muslim countries, such as dependence on capitalist economic systems and social inequalities exacerbated by globalization, as well as opportunities to develop sharia economics and increase cooperation between Muslim countries. By leveraging digital technology and just Islamic principles, Muslim countries can develop more inclusive, sustainable and just economic systems, which can have a positive impact not only on the Muslim world, but also on global prosperity.